Ensino remoto e saúde mental: vivências de estudantes do ensino médio - Silva, Carla Leitão da (Universidade Federal de São Carlos, 2023)
The social distance imposed by covid-19 suddenly changed human interactions. For a long time, schools operated only through remote teaching. By using digital means, remote learning could not serve all students, negatively impacting the schooling processes of a significant portion of this population. Moreover, removing this interaction environment typical to young people meant that many students did not have the experiences that many of these subjects would have without the context of the pandemic. During this period, difficulties in the schooling process, including excessive work and tests and low future perspectives, were recurrent reports from young people. All these aspects were pointed out as causing psychosocial suffering in young people during the remote education period. Thus, this research aims to understand how remote learning and its consequences impacted the mental health of young high school students. To this end, the fieldwork was developed using two synchronous online focus groups with high school students from the cities of Santos, São Paulo, and Sorocaba, who are members of Scientific Initiation to High School (IC-EM) projects. The results obtained through this study indicate that the main complaints of these students included: (1) disorganization of classes; (2) lack of emotional support from schools; (3) uncertainties about their choice of profession; (4) feelings of little or no school learning; and (5) reports of bullying. In addition, we identified which strategies these young people used to face possible episodes of mental suffering.
Remote teaching and mental health: experiences of high school students
Keywords: Juventude; Ensino remoto; Ensino médio; Saúde mental; Youth; Remote learning; High school; Mental health; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO